Randomized Comparative Clinical Trial of Udumbar Kshara Sutra Andsnuhi Kshara Sutra with Standard Apamarg Kshara Sutra in the Patient of Bhagandara (Fistula in Ano) - Kumari Nidhi Shree Bibhuti (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Bhagandara(fistula in ano) is one of the commonest diseases occurring in ano-rectal region. The incidence of a fistula-in-ano developing from an anal abscess ranges from 26% to 38%. The surgical management of Bhagandara caries several problems and complications as severe pain for a long period during dressing. Operative raw site is the potential space for infection by faeces. Hospitalization and non-ambulatory life for a long period, Retention of urine, Incontinence. Ksharasutra is a successful novel drug delivery system in which a special thread smeared with Kshar and other herbs is applied to induce both mechanical and chemical effect which helps in cutting and healing of the Fistula tract. In this clinical study total 30 patients of Bhagandara was registeredfrom OPD and IPD of Shalya Tantra department, Major S.D. Singh P.G. Ayurvedic Medical College, Farrukhabad, and randomly divided in three groups. In this comparative clinical study all the subjective parameters like pain, itching and objective parameter like swelling, discharge, unit cutting time showed statistically significant results in all groups.It was found that Udumbar Ksharasutra was more effective than Snuhi & Apamarg Ksharasutra. It is cost effective and easy to apply & Patient treatedwith Udumbar Ksharasutra found better than Snuhi & Apamarg. Hence, it can be used as an alternative approach for management of Bhagandar.